A performance measurement decision support system method applied for technology-based firms' suppliers. Issue 1 (2nd January 2017) - Siluk, Julio Cezar Mairesse; Kipper, Liane Mahlmann; Nara, Elpidio Oscar Benitez; Neuenfeldt Júnior, Alvaro Luiz; Dal Forno, Ana Júlia; Soliman, Marlon; Chaves, Daniel Marques da Silva
Abstract: The present article proposes a mathematical decision support system model to measure the performance of incubated technology-based firms (TBFs) suppliers. The research was conducted based on three steps: (1) a literature review, in order to parameterise the research in relation to the theme; (2) the construction of a measuring system, based on the presumptions permeated by the analytic hierarchy process (AHP); and (3) the application of the system at three companies. The findings demonstrated the mathematical modelling developed is capable of providing satisfactory results to the reality of the sector studied, presenting the situation of the suppliers evaluated, independent of the nature of the indicated critical success factors (CSFs). Also, this tool supports companies by providing a strong foundation to organise the information regarding the service level delivered by each supplier, according to previous research on the theme.